The international dimension of confidence shocks - Stéphane Dées; Jochen Güntner (Johannes Kepler University of Linz, Department of Economics, 2014)
Building on Beaudry, Nam and Wang (2011) - hereafter BNW -, we use survey data on consumer sentiment in order to identify the causal effects of confidence shocks on real economic activity in a selection of advanced economies. Starting from a set of closed-economy VAR models, we show that these shocks have a significant and persistent impact on domestic consumption and real GDP. In line with BNW, we find that confidence shocks explain a large share of the variance in real economic activity. At the same time, the shocks we identify are significantly correlated across countries. In order to account for common global components in international confidence cycles, we extend the analysis to a FAVAR model. This approach proves effective in removing the correlation in country-specific confidence shocks and in isolating mutually orthogonal idiosyncratic components. As a result, the (domestic and cross-border) impacts of country-specific confidence shocks are smaller and their contribution to business cycle fluctuations is reduced, confirming the global dimension of confidence shocks. Overall, our evidence shows that confidence shocks play some role in business cycle fluctuations. At the same time, we show that confidence shocks have a strong global component, supporting their role in international business cycles.
Keywords: C32; E17; E32; F41; 330; Consumer Confidence; Consumption; International Linkages; Vector Autoregression (VAR); Factor-Augmented VAR (FAVAR)